Pengaruh Scramble Berbasis IT Dalam Meningkatkan Pemahaman Tarakib Nahwiyyah - Dodi Robiansyah; Rohid Vatullah; Ii Rahmanudin; Burhan Lukman Syah (Unversitas Muhammadiyah Mataram, 2022)
Abstract: Scramble learning model is a learning model that provides an interesting and fun learning atmosphere. In addition, this learning model can improve student responsiveness during learning because it is required to actively develop creativity and think to solve tarakib problems using this model. Scrambel has often been used in general lessons but not in Arabic lessons. So that the purpose of this study can be taken to find out Arabic learning in tarakib understanding of the material